Komplikace operačního léčení zlomenin acetabula - Pavelka, Tomáš; Houček, Petr (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2009)
PURPOSE OF THE STUDY To analyse retrospectively complications of the surgical treatment of displaced acetabular fractures. MATERIAL In the years 1996 to 2006 a total of 251 patients with acetabular fractures were treated. The group comprised 162 men and 89 women; the average age was 35 years. The average follow-up was 71 months (range, 16 to 138). Based on the AO classification, type A fractures were found in 58 %, type B in 23 % and type C in 19 % of the patients. Indications for surgical intervention were hip instability or hip incongruence. RESULTS The complications included intra-operative, and early and late post-operative problems. Of the intra-operative complications, 2 % were vascular injuries, 5 % were damage to the static nerve, 13 % were due to incomplete reduction and 2 % due to bone non-union. Early post-operative complications in five patients (2 %) required revision surgery for early infection in two, haematoma in the wound in one and failed osteosynthesis in two patients. In one patient failed osteosynthesis was associated with hip dislocation. Late complications included aseptic necrosis in 7 %, post-traumatic arthritis in 17 %, para-articular ossification grades III and IV of the Brooker classification in 7 % and late infection in 0.5 % of the patients. DISCUSSION The outcome of surgical treatment depends on quality reconstruction of the articular surface and complications, and is related to the fracture type and method of treatment. Not every poor outcome means it is a complication, nor is it always related to the type of fracture. Some fracture types are bound to heal poorly. The complex anatomy of the joint involves rather frequent injury to nerve structures and imperfect reduction and fixation. CONCLUSIONS The most frequent complication is the development of post-traumatic arthritis due to imperfect reduction. However, the current limit of achieving correct reduction and weight-bearing surface reconstruction remains an open issue. Aseptic necrosis in type A fractures was three-times as high as in type B and C fractures. Imperfect reconstruction of the acetabulum and failure to restore hip joint congruence were twice higher in type B than type A and C fractures.
Keywords: dospělí; vnitřní fixace fraktury; Aged; Young Adult; senioři; lidé středního věku; Adolescent; Female; dítě; mužské pohlaví; mladý dospělý; fraktury kostí; Postoperative Complications; acetabulum; lidé; Fractures, Bone; Intraoperative Complications; peroperační komplikace; Acetabulum; Child; Middle Aged; ženské pohlaví; Humans; Male; pooperační komplikace; Fracture Fixation, Internal; Adult; mladiství